Efektivitas Pembelajaran Mendalam Berbantuan Geogebra terhadap Kemampuan Berpikir Kritis Siswa pada Bangun Ruang Sisi Datar - Edy Supratman; Daroe Iswatiningsih (Media Pendidikan Matematika, 2025)
This study aims to examine the effectiveness of deep learning assisted by GeoGebra on students’ critical thinking skills in the topic of Three-Dimensional Geometry (Polyhedrons) among eighth-grade students at SMPN 3 Lingsar. This research employed a quasi-experimental design with a Pretest-Posttest Control Group Design. The sample consisted of two classes: the experimental class, which received deep learning assisted by GeoGebra, and the control class, which received conventional instruction. The research instrument was an essay test measuring five indicators of critical thinking: interpretation, analysis, evaluation, inference, and conclusion. Data were analyzed using an independent t-test with SPSS version 25. The results revealed a significant difference in critical thinking skills between the experimental and control classes, with a significance value of Sig. (p) = 0.000 < 0.05. This finding indicates that deep learning assisted by GeoGebra is more effective than conventional learning. In addition to improving learning outcomes, this approach promotes active engagement, motivation, and students’ reflective abilities. Therefore, GeoGebra has proven to be a powerful tool to enhance 21st-century learning implementation, emphasizing the development of critical, independent, and creative thinking in understanding mathematical concepts more deeply.